Economic analysis of grain production systems with annual winter pastures, under no-tillage - Fontaneli, Renato Serena; Ambrosi, Ivo; Santos, Henrique Pereira dos; Ignaczak, João Carlos; Zoldan, Sandra Maria (Pesquisa Agropecuaria Brasileira, 2000)
During six years (1990 to 1995), at the CEPAGRO-Centro de Extensão e Pesquisa Agronômica, of the Faculdade de Agronomia da Universidade de Passo Fundo, in Passo Fundo, RS, Brazil, the effects of grain production systems and annual winter pastures were assessed. The economic analysis on that period is presented in this paper. Four production systems were evaluated: system I (wheat/soybean, grazed black oats/soybean, and grazed black oats/soybean); system II (wheat/soybean and grazed black oats + grazed common vetch/pasture/corn); system III (wheat/soybean, grazed black oats + grazed common vetch/soybean, and grazed black oats + grazed common vetch/corn); and system IV (wheat/soybean, white oats/soybean, and white oats/soybean). An experimental design in blocks at random, with three replications and plots with 500 m2, was used. In the average of six years, system II showed a higher net return (R$ 432.71/ha), as compared to system IV (R$ 322.93/ha). System II showed no significant differences in relation to systems I (R$ 377.93/ha) and III (R$ 400.27/ha). The integration crop-livestock under no-tillage was viable for both winter and summer crops, as well as for fattening beef cattle during winter time.